A comparative study between yarn diameter and yarn mass variation measurement systems using capacitive and optical sensors - Carvalho, Vítor (2008)
This paper reports a comparative study between yarn mass and yarn diameter measurement systems using a deferential capacitance tester and au optical coherent signal processing diameter tester respectively. A full description of the systems is presented along with their new contributions, namely 1 mm length samples analysis for a capacitive tester and optical signal processing lo eliminate the influence of hairiness while measuring the diameter. It is proven statistically that the yarn mass measurement systems based on capacitive testers give similar results to that of optical diameter measurement system when identical yarn samples are used. A detailed test report of a cotton yarn with a linear mass of 295 g/km is presented.